Design and Feasibility Evaluation of a Web-Based Container Damage Reporting Information System for Container Terminal Operations - Kencana Verawati; Mohd Faizal Sulaiman; Rully Indrawan; Euis Saribanon; Siti Maemunah; Arsad Rifki Adhawi Fareza (Universitas Amikom Yogyakarta, 2026)
Purpose: This research designs and evaluates a web-based information system for Container Damage Report (CDR) management in container terminal operations. The study emphasizes applied computing, browser-based access, cloud data storage, and human-centered operational usability. The previous CDR process relied on paper forms, verbal confirmation, and separate photo files, resulting in slow retrieval, inconsistent documentation, and limited traceability. Methods: The research applied the 4D development model consisting of define, design, develop, and disseminate stages. The define stage identified operational problems, user roles, data needs, and reporting constraints through field observation, interviews, workflow review, and document analysis. The design stage formulated the reporting flow, required fields, database structure, interface layout, and access mechanism. The development stage implemented a no-code cloud prototype by integrating Tally for online input, Google Sheets for centralized records, and Google Sites as a web portal. The dissemination stage involved a limited introduction and user-acceptance testing. Results: The prototype supports structured online input, photo evidence upload, timestamped records, centralized cloud storage, browser-based retrieval, and monitoring of report status. User validation yielded scores of 76%, 94%, and 84%, with an average of 84.67%, indicating that the prototype is feasible for initial operational use. Novelty: The study contributes a lightweight applied computing model for container damage reporting. It shows how no-code cloud tools can support an affordable transitional architecture before integration with enterprise terminal operating systems.